Ureidoglycolate Synthetase of Streptococcus allantoicus II. Properties of the Enzyme and Reaction Equilibrium - Gaudy, Elizabeth T. (1965)
Gaudy, Elizabeth T. (University of Illinois, Urbana), and R. S. Wolfe. Ureidoglycolate synthetase of Streptococcus allantoicus. II. Properties of the enzyme and reaction equilibrium. J. Bacteriol. 90:1531–1536. 1965.—The properties of ureidoglycolate synthetase from Streptococcus allantoicus grown on allantoin were studied, by use of the purified enzyme preparation and crystalline sodium ureidoglycolate. Ureidoglycolate synthetase activity was maximal over the pH range of 8.4 to 8.8. No cofactors were required for the reaction. Enzyme activity was inhibited by p-chloromercuribenzoate at relatively high concentrations, by Hg(++) or Zn(++) ions, and to a lesser extent by several other metal cations. The maximal velocity for the purified ureidoglycolate synthetase, determined graphically from a Lineweaver-Burk plot, was 220 μmoles of glyoxylate formed per min per mg of protein. The substrate concentration required for half-maximal velocity was 3.3 × 10(−2)m. The equilibrium constant for the synthesis of ureidoglycolate was determined in a series of reaction mixtures covering a wide range of initial concentrations of reactants. The position of the equilibrium was not affected by a change in pH or by the presence of enzyme. The equilibrium constant for the reaction in the direction of synthesis was 7.6, corresponding to a negative free energy change of 1,230 cal per mole.